Acute Pancreatitis after Additional Trauma in Chronic Traumatic Pancreatic Diaphragmatic Hernia - You Ho Mun; Sin Youl Park (Journal of Trauma and Injury)
Traumatic diaphragmatic injuries (TDIs) are a rare complication in thoraco-abdominal trauma. The diagnosis is difficult and if left untreated, TDI can cause traumatic diaphragmatic hernia (TDH). Through an injured diaphragm, the liver, spleen, stomach, small intestine, and large intestine can be herniated to the thoracic cavity, but pancreatic herniation and pancreatitis are quite rare in TDH. This paper reports a case of pancreatitis developed by additional trauma in a patient with asymptomatic chronic TDH. A 58-year-old male visited the emergency department with a left abdominal injury after a fall 6 hours earlier. The vital signs were stable, but the amylase and lipase levels were elevated to 558 U/L and 1,664 U/L, respectively. Abdominal computed tomography (CT) revealed a left diaphragmatic hernia and an incarceration of the stomach, pancreatic ductal dilatation, and peripancreatic fatty infiltration. Additional history taking showed that he had suffered a fall approximately 20 years ago and had an accidentally diaphragmatic hernia through a chest CT 6 months earlier. A comparison with the previous CT revealed the pancreatitis to be caused by secondary pancreatic ductal obstruction due to the incarcerated stomach. For pancreatitis, gastrointestinal decompression was performed, and after 3 days, the pancreatic enzyme was normalized; hence, a thoracotomy was performed. A small ruptured diaphragm was found and reposition of the organs was performed. This paper reports the experience of successfully treating pancreatitis and pancreatic hernia developed after trauma without complications through a thoracotomy following gastrointestinal decompression.